Weight Loss Intervention in Young Adults with Severe Learning Disabilities: The Additive Effect of Cognitive Behavioral Treatment (a Pilot Study) - Vaisman, Nachum; Regev, Rachel; Katalan, Lior; Duani, Yael (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
The prevalence of obesity is reported to be higher among people with intellectual disabilities compared to the general population. Factors which were suggested to contribute to this increased prevalence include: low adherence to healthy diets, poor level of physical activity, intellectual disabilities and the lack of residential settings supporting independence. This study was designed to evaluate the additive effect of an intervention in the form of cognitive behavioral treatment (CBT) in a multi-strategy weight loss program for young adults with severe learning disabilities living in group residences in the community. The study population included 28 subjects (12 males) who were randomly assigned to one of two groups. Both groups had a weekly meeting with a dietician and were invited to take part in walking groups. One group (intervention group) had on top a weekly session of CBT. The results of our study indicate that adding a CBT component to a conventional program aiming at improved nutritional understanding (prudent diet, physical activity) of subjects with LD may improve the success for change in life habits, yet, in our study this effect was noticeable only on follow up few months after study termination. Neither group differences at baseline nor differences in the scoring for the locus of control questionnaire at baseline could predict this outcome. This delayed impact warrants further investigation.